Quality management of Zarrineh Rud river for agricultural irrigation using QUAL2K simulation model - Jalalzadeh, Armin; Rabieifar, Hamid Reza; Vosoughifar, Hamid Reza; Razmkhah, Arash; Fataei, Ebrahim (Journal of Environmental Engineering and Landscape Management, 2022)
Zarrineh Rud river is one of the most important rivers in northwest of Iran. In this study, QUAL2K simulation model was used. The simulation parameters in this study were collected from 5 sampling stations. The results showed that the amount of oxygen saturated solution of Zarrineh Rud river varied between 7–8 mg / l, which is higher than the maximum standard value required. The results showed that BOD could increase by 16%, respectively, and should decrease by 70%. The station S5 at the river downstream with 3.53 mg/L DO deficit was the most critical point, and the 26th kilometer of the river with a DO deficit of 2.05 mg/L was the most critical point for maintaining the aquatic life; therefore, some scenario must be developed for waste load reduction at this station. In order to improve the quality of Zarrineh Rud river, construction of a wastewater treatment plant is necessary for Miandoab sugar factory.